Synergistic bactericidal combinations between gentamicin and chitosan capped ZnO nanoparticles: A promising strategy for repositioning this first-line antibiotic - Scolari, Ivana Romina; Paez, Paulina L.; Granero, Gladys Ester (2024)
Impact Factor: 3.4